A methodology for risk based decision making in a service oriented environment - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S. (IEEE Computer Society, 2006)
Decision making is a complex process. It involves dealing with a lot of uncertainty and projecting in mind what the final outcome might be at the end. Based on the projection of the final outcome a decision is taken. Decision making in a peer-to-peer financial interaction is a further complex process as it also involves with considering the possible financial loss to the trusting agent in the interaction. In this paper we ease the decision making process of a trusting agent to decide whether to interact with a trusted agent or not or choose a particular trusted agent to interact with, by proposing an approach that analyzes the Risk that could be present in interacting with it.